New spectral templates for rhodopsin and porphyropsin visual pigments - Gačić, Zoran; Mićković, Branislav; Gačić, Luka; Damjanović, Ilija (Archives of Biological Sciences, 2019)
Paper description: We compared a model for spectral sensitivity data designed in our laboratory with the widely used template. Our model was designed with fewer (four) parameters, which we believe brings us closer to understanding the true nature of the absorption curve. In the fitting of spectral sensitivity data it uses non-transformed wavelengths. As a result, the shape of the curve remains the same for a broad range of lmax values. Abstract: A four-parameter model of spectral sensitivity curves was developed. Empirical equations were designed for A1- and A2-based visual pigments with the main a-band maximum absorptions (lmax) from 350 nm, near the ultraviolet, up to 635 nm in the far-red part of the spectrum. Subtraction of the a-band from the full absorbance spectrum left a “b-band” described by a lmax-dependent Gaussian equation. Compatibility of our templates with A1-and A2-based spectra was tested on the electroretinographic (ERG-derived) scotopic action spectra recorded in dogfish shark, eel, Prussian carp and perch. To more precisely estimate the accuracy of our model, we compared it with widely used templates for visual pigments. There was almost no difference between the tested models in fitting the above-mentioned spectral data. One of the advantages of our model is that in the fitting of spectral sensitivity data it uses non-transformed wavelengths and the shape of the curve remains the same for a broad range of lmax values. Compared to multiparameter templates of other authors, our model was designed with fewer (four) parameters, which we believe can bring us closer to understanding the true nature of the absorption curve. https://doi.org/10.2298/ABS180822052G Received: August 22, 2018; Revised: November 7, 2018; Accepted: November 14, 2018; Published online: November 20, 2018 How to cite this article: Gačić Z, Mićković B, Gačić L, Damjanović I. New spectral templates for rhodopsin and porphyropsin visual pigments. Arch Biol Sci. 2018;71(1):103-10.